Tooth size and dental arch dimensions in different types of crowding in Malay population - Saeed, Nazik Abdullah Mustafa (2018)
The aim of this research is compare tooth size and dental arch dimensions between different types of crowding i.e. mild, moderate, and severe crowding, in the Malaysian population. Tooth size parameters under investigation were mesiodistal widths, buccolingual widths and tooth size ratio (Bolton Indexes) and arch dimension parameters were arch perimeters, arch widths, arch depth and arch ratio (Pont’s Indexes). This study was carried out at the School of Dental Sciences, Universiti Sains Malaysia (USM), on a sample involving 192 dental models of male and female subjects with the age range of 18 to 35 years old and no history of previous orthodontic treatment collected from the archive of orthodontic clinic. Scanning were done with Hirox digital stereomicroscope (SM) for the fabrication of the digital models to investigate the tooth size and arch dimensions of both maxillary and mandibular arches for each subject. ANOVA was used to compare tooth size and arch dimensions as well as the Bolton and Pont’s Indexes in different types of crowding.There were only a few measurements of the tooth size and arch dimensions which showed significant difference in different types of crowding. Both Bolton’s and Pont’s indexes also did not show significant difference. In conclusions, tooth size, arch dimensions, Bolton Indexes and Pont’s Indexes were not different in different types of crowding in Malaysian population. The aetiology of crowding were not related to individual tooth sizes and arch dimensions but rather a combination of these factors.